Knowledge, attitudes and practice toward refractive errors management among left-behind children of migrant workers - Shuang Liu; Guang Yang; Qingnan Li; Ruxia Pei; Shaohua Tang (Frontiers in Public Health)
BackgroundThis study aimed to access knowledge, attitudes and practice (KAP) regarding refractive errors (RE) management among the left-behind children of migrant workers.MethodsThis cross-sectional study was performed by the Ophthalmology Department of Beijing Jishuitan Hospital between July and August, 2023. The KAP scores were assessed using a self-designed questionnaire.ResultsAnalysis of 350 questionnaires showed mean KAP scores of 9.21 ± 3.00 (possible range 0–14), 33.23 ± 3.57 (possible range 9–45), and 50.19 ± 5.31 (possible range 14–70), respectively. Pearson’s correlation analysis showed positive correlation was found between knowledge and practice (r = 0.286, p < 0.001), negative correlation between knowledge and attitude (r = −0.150, p = 0.005), and positive correlation between attitude and practice (r = 0.141, p = 0.008). Multivariate logistic regression analysis showed that children’s age (OR = 0.748, 95%CI: 0.632–0.885, p = 0.001), duration away from parents (OR = 0.345, 95%CI: 0.172–0.691, p = 0.003) and RE in parents (OR = 0.405, 95%CI: 0.218–0.753, p = 0.004) were independently associated with knowledge. Relationship to the child other than grandparent (OR = 0.252, 95%CI: 0.064–0.999, p = 0.050), as well as child’s gender (female, OR = 1.671, 95%CI: 1.006–2.777, p = 0.047) and duration of sleep per day (OR = 8.401, 95%CI: 1.473–47.923, p = 0.017) were independently associated with practice. In addition, structural equation modeling also showed positive impact of knowledge on practice (β = 1.251, p < 0.001).ConclusionLeft-behind children of migrant workers have mostly sufficient knowledge, positive attitude and proactive practice toward RE management, significantly influenced by child’s age, relationship with the child, and duration of living without parents.